Calidad microbiológica del agua potable de acuerdo a la normativa ecuatoriana nte inen 11.08:2014 - Vega Herrera, Jose Octavio (Machala : Universidad Técnica de Machala, 2019)
Gastrointestinal infection resulting from the consumption of contaminated drinking water for domestic use prevails due to inadequate control of intra-residential sanitary activities, there are currently routine controls by the Ministry of Public Health that routinely control the quality of drinking water in its distribution networks and in this way they guarantee that the water reaches its destination (home) free of microorganisms, but it does not guarantee the storage or distribution networks within the homes. The presence of coliforms in drinking water are indicators of faecal contamination that lead to digestive disorders such as diarrhea, cholera, dysentery, among other pathologies manifested by Gram-negative bacteria whose origin is the human and animal digestive tract. The present work has as objective to evaluate the microbiological quality of the water by means of bibliographical revision to establish if it is suitable for human consumption. It is based on a qualitative-quantitative study: qualitative because the presence of fecal and total coliforms is determined by the membrane filtration method and quantitative by the quantification of Colony Forming Units (CFU) and confirmation by the Probable Numerous (NMP) method. , according to the Ecuadorian Technical Regulations Based on the study of 28 samples from different houses, it was possible to identify that microbial contamination factors lie in personal hygiene and poor intra-residential storage processes. It is proposed to avoid storage without proper control of regulatory entities ( MSP) and establish biosafety standards in homes that motivate to avoid possible risks of microbial contamination.
La infección gastrointestinal producto del consumo de agua potable contaminada de uso doméstico prevalece debido a un inadecuado control de las actividades sanitarias intradomiciliarias, actualmente existen controles rutinarios por parte del Ministerio de Salud Pública que controlan rutinariamente la calidad de agua potable en sus redes de distribución y de tal forma garantizan que el agua llegue a su destino(hogar) libre de microorganismos, pero no garantiza el almacenamiento o redes de distribución dentro de los hogares. La presencia de coliformes en agua potable son indicadoras de contaminación fecal que conllevan a alteraciones digestivas como diarrea, cólera, disentería, entre otras patologías que se manifiestan por bacterias Gram negativas cuya procedencia es el tracto digestivo humano y animal. El presente trabajo tiene como objetivo evaluar la calidad microbiológica del agua mediante revisión bibliográfica para establecer si es apta para el consumo humano. Se basa en un estudio cuali-cuantitativo: cualitativo por que se determina la presencia de coliformes fecales y totales mediante el método filtración de membrana y cuantitativo por la cuantificación de Unidades Formadoras de Colonias (UFC) y confirmación por el método Numerosas Probable (NMP),según las Normativa Técnica Ecuatoriana En base al estudio de 28 muestras de diferentes casas se logró identificar que los factores de contaminación microbiana radican en la higiene personal y malos procesos de almacenamiento intradomiciliario Se plantea evitar el almacenamiento sin el control adecuado de los entes reguladores (MSP) y establecer normas de bioseguridad en los hogares que motiven a evitar posibles riesgos de contaminaciones microbianas.
Keywords: CONTROL; CALIDAD; AGUA; MICROORGANISMOS